The Influence of Interpersonal Competence on Job Satisfaction of Junior High School Teachers in Muaro Jambi Regency - Pitriyani; Firman; Rosmiati; Bunga Ayu Wulandari (proceedings.icesy, 2026)
This study aims to directly obtain empirical evidence regarding the influence of interpersonal competence on job satisfaction of public junior high school teachers in Muaro Jambi Regency. The study employed an associative quantitative approach with a correlational survey design, analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that the hypothesis was significant. Interpersonal competence has a direct effect on job satisfaction. This model is rarely applied to teacher job satisfaction research, particularly in the regional context. Another important contribution is the provision of empirical evidence based on local data from Muaro Jambi Regency, which can serve as a basis for formulating more comprehensive policies to improve teacher welfare and performance. This study has limitations such as its cross-sectional design, limited coverage area, and the use of perceptual data. Nevertheless, the research findings still provide conceptual and practical contributions to efforts to improve the quality of human resources in the education sector.